Wear behaviour of Al-SiC and Al-Al2O3 matrix composites sliding against automobile friction material - Fu, P.R.K.; Sujan, Debnath; Oo, Zeya; Gorin, A.; Liew, W.Y.H. (American Institute of Physics, 2013)
This paper presents a study on the wear behaviour of metal matrix composites (MMC), which is a criterion for potential material for the development of the automotive brake disc. The wear tests have been carried out on a wear and friction monitor machine, using commercial automobile brake pad as pin and Al-SiC MMC and Al-Al2O3 MMC as discs. Pins have been machined from commercial automobile brake pad of a passenger car. The Al-SiC MMC and Al-Al2O3 MMC discs have been fabricated by stir casting technique using BS 1470 aluminium alloy; 5 wt%, 10 wt% and 15 wt% of silicon carbide particles and alumina particles. The friction and wear behavior of MMCs and the automobile brake pad pins have been investigated at two applied loads; 5N and 10N. The worn surfaces formed on the MMCs discs have been analysed using scanning electron microscopy (SEM). The present investigation shows that the MMCs have considerable stable friction coefficient.